Analysis of the Implementation of ITIL V3 Domain Service Operation in Enhancing the Quality of Information Technology Services - Fauzan, Kiagus Rachmat; Nurdianto, Imam Bayu; Muhammad, Yudhistira; Santosa, Muhammad Wildan; Prakoso, Osara Gandang; Wijanarko, Aris; Tarwoto (Bright Institute, 2023)
The rapid growth in the hotel industry in Purwokerto has given rise to new challenges related to the management and provision of information technology services. In the midst of increasingly fierce competition, the success of a hotel depends not only on the quality of service but also on the effectiveness of the information technology systems that support its operations. To overcome this complexity, Hotel ABC Purwokerto has adopted the ITIL V3 Domain Service Operation approach in managing its information technology services. This article aims to provide comprehensive insight into how hotels can optimize their operations through effective information technology service management. The use of the ITIL V3 Domain Service Operation framework at Hotel ABC is not only a solution to respond to rapid changes in information technology but also an effort to meet the high expectations of guests who are increasingly smart and technology-savvy. Through careful analysis, this article will reveal how implementing ITIL V3 at the operational level can have a positive impact on the efficiency, reliability and innovation of information technology services provided by Hotel ABC. By understanding the context and problems faced by Hotel ABC Purwokerto, we can explore in more depth how ITIL V3-based information technology service management strategies can be the key to success in improving service quality and maintaining competitiveness in this dynamic hotel industry.